Legal Framework for Corporate Governance in Nigeria: An Appraisal of the 2018 Code of Corporate Governance - Amujo–Akomolafe, Monica (ABUAD Private and Business Law Journal, 2018)
Corporate Governance deals with the decision-making structures of corporations and organizations and establishes a relationship between shareholders’ interests such as investors and owners of the issued shares of the corporation and other stakeholders’ interests such as employees, customers, suppliers, individuals where the corporation interacts, etc. Great corporate governance is necessary for setting standards required by corporations to establish a distinctive business environment. Over the years there has been no uniform code on corporate governance of general application to regulate and monitor corporate governance in Nigeria. Therefore the study seeks to undertake an examination of the historical background as well as the processes and structure of corporate governance. In particular, the paper will carry out a critical review of the 2018 Nigerian Code of Corporate Governance (NCCG), the latest legal framework on corporate governance unveiled by the Minister for Industry, Trade and Investment on January 15, 2019. The paper will rely on both primary and secondary sources of data. Primary sources are legislations and judicial decisions. Secondary sources are books, journal, online articles and periodicals. The paper concludes that 2018 NCCG is in line with international best practices as it primarily seeksto institutionalize the maximum standard of corporate governance in Nigeria and sensitize the public on the significance of upholding corporate values and principles. The paper recommends that regulatory authorities and all interested parties in the corporate world must collaborate to ensure adequate compliance with the code for the attainment of an effective system of corporate governance in Nigeria.